Kajian Literatur Sistematis Desain User Interface dan User Experience Media Animasi Dalam Meningkatkan Konsentrasi Anak Berkebutuhan Khusus Tunagrahita - Ersania, Ayu Bella; Julianto, I Nyoman Larry; Swandi, I Wayan (Fakultas Seni Rupa dan Desain ITB, 2025)
This systematic literature review investigates the role of User Interface (UI) and User Experience (UX) in animated learning media for enhancing the concentration of children with intellectual disabilities. Drawing from 30 selected publications, the study highlights previous findings that well-designed digital media can significantly improve learning outcomes for children with special needs. Using inclusive criteria, the researchincorporates observations of learning environments and interviews with educators at SLB Negeri 2 Denpasar. The effectiveness of UI/UX elements is assessed through the Questionnaire for User Interface Satisfaction (QUIS) and the User Experience Questionnaire (UEQ). Key insights emphasize the impact of intuitive and engaging design in sustaining concentration and aiding comprehension. The study offers practical guidelines for developing accessible and effective learning tools, underscoring the importance of inclusive design practices in special education and providing a valuable foundation for future educational technology advancements.